2009
DOI: 10.2298/hel0951033s
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in sunflower after mutagen treatment of immature embryos of different ages

Abstract: The frequency and spectrum of morphological and physiological mutations obtained in M 2 and M 3 generations after sunflower immature embryos treatment with ethyl methanesulphonate (EMS) have been studied. Immature 9 -10 and 14 -15-day-old embryos of two genotypes were treated with EMS at the concentration of 0.02% for 16 hours. Thirty-three types of mutation were found, described, and classified into the following groups: chlorophyll deficiency (3 types), cotyledon mutation (1), leaf mutations (6), stem mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…We observed dwarf plants, full sterile plants, plants with decrease number of ray flowers, early flowering plants, malformed leaf, split leaf blades, fan- shaped venation, small and malformed capitulum, absence of ray florets, decreased number of ray florets and replacement of ray leaves with bract leaves. Some of these mutations were published by Soroka and Lyakh (2009) after treatment of immature zygotic embryo with EMS. In our study some mutant plants were isolated and self-pollinated for several generations.…”
Section: Results and Discusionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed dwarf plants, full sterile plants, plants with decrease number of ray flowers, early flowering plants, malformed leaf, split leaf blades, fan- shaped venation, small and malformed capitulum, absence of ray florets, decreased number of ray florets and replacement of ray leaves with bract leaves. Some of these mutations were published by Soroka and Lyakh (2009) after treatment of immature zygotic embryo with EMS. In our study some mutant plants were isolated and self-pollinated for several generations.…”
Section: Results and Discusionmentioning
confidence: 99%
“…Costov et al (2007) increased resistance of tomato to Orobanche ramosa L. by application of EMS. Thirty-three types of chemical mutation at sunflower immature embryos were found, described and classified by Soroka and Lyakh, 2009. Encheva et al (1993, 2003 have reported statistically significant changes in morphological characters of plants regenerated from immature zygotic embryos of sunflower, independently and in combination with gamma irradiation or ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, when plants with indeterminate inflorescences were kept under drought conditions prior to flowering and then subjected to heavy watering and high nutrient levels, they produced numerous fasciations (Hus 1908). Ionizing radiation and chemical agents also caused fasciation in stems and inflorescences (Johnson 1926;Irvine 1940;Behera and Patnaik 1981;Drjagina et al 1981;Gottschalk and Wolff 1983;Jambhulkar 2002;Soroka and Lyakh 2009;Abe et al 2009). Application of some plant growth regulators causes fasciation.…”
Section: Physiological Fasciationmentioning
confidence: 99%
“…It occurs in the morphology of plant organs and typically involves broadening of the shoot apical meristem, flattening of the stem, and changes in leaf arrangement (Iliev & Kitin 2011). It has been noted that many biotic and abiotic causes lead to the development of fasciated forms including fungal and nematode infections (Stange et al 1996) and mineral deficiency; zinc deficiency is known to cause fasciation (Rance et al 1982), temperature fluctuation (Binggeli 1990), chemical mutagens (Soroka & Lyakh 2009), and mutations (El-Banna et al 2013). Fasciation is a frequent phenomenon in Cactaceae and in many other succulents' family like in Euphorbiaceae, Crassulaceae, and Asclepiadaceae.…”
Section: Introductionmentioning
confidence: 99%